FACTOR AFFECTING PERCEIVED USEFULNESS IN FOOD AND BEVERAGE TECHNOLOGY: 4 AND 5 STARS HOTEL IN KUALA LUMPUR, MALAYSIA - Muhamad Stamam, Muhamad Syahir; Ahamad, Mohd Naim; Cpt. Zainudin, Eti Farah; Ahmad Rashidi, Abdul Rahman Redha (Journal of Techno-Social, 2013)
Technology is defined as a tool or machine that helps to fulfill task to become easier. Indeed, the worldwide used of technology has been accepted as one of the factors which help the hotel employees to fulfill their tasks efficiently and productively. Despite of its universal benefits to the development of the hotel industry, the acceptance of hotel employees towards the usage of technology is still uncertain and imprecise. This study is conducted to investigate what are the external factors that influence to the employees’ acceptance on the usage of technology in hotel daily operations. At this intensity, the employees were required to express their experiences in using the technology application installed within the operations of their hotel institution. In addition, this study is focusing on Point of Sales (POS) System used in the hotel coffee house operation.The sample population of this study was among the front liners who are working atthe coffee house operation. Questionnaires were distributed to 31 four and five stars rated hotels located in Kuala Lumpur. A series of analyses looking at the mean score, multicollinearity, frequencies, and standard deviation through descriptive and parametric statistic were undertaken. Overall, some useful information was obtained. Technology Acceptance Model (TAM) shown that there are two mediating effects that will influence the relationship between external variable and individual acceptance towards the system use.Results reveal that, task fit is an external variable that will affect the acceptance of a user towards technology. Moreover, based on the data gathered, it proves that task fit will lead to the perceived usefulness of technology.